Pacing and Sensing of Human Heart for over 31 Years with the Same Apparatus (Generator and Lead) - Evangelos Papasteriadis; Panagiotis Margos (Case Reports in Cardiology)
Several patients receive a permanent pacemaker in a relatively young age, with multiple subsequent reoperations for pacemaker replacement. Pulse generator replacement is an invasive procedure, associated with the risk of various complications, mainly infection and skin erosion. A case of an extremely long-lasting pacemaker with a totally uneventful longevity period over 31 years is presented. The explanation for this quite rare pacemaker longevity (possibly unique) is analyzed and discussed.